Predominant mucosal IL-8 mRNA expression in non-cagA Thais is risk for gastric cancer - Sirikan Yamada (2018)
Aim: To study gastric mucosal interleukine-8 (IL-8) mRNA expression, the cytotoxin-associated gene A (cagA) mutation, and serum pepsinogen (PG) I/II ratio related risk in Thai gastric cancer. Methods: There were consent 134 Thai non-cancer volunteers who underwent endoscopic narrow band imaging examination, and 86 Thais advance gastric cancer patients who underwent endoscopic mucosal biopsies and gastric surgery. Tissue samples were taken by endoscopy with 3 points biopsies. The serum PG I, II, and Helicobacter pylori (H. pylori) immunoglobulin G (IgG) antibody for H. pylori were tested by enzyme-linked immunosorbent assay technique. The histopathology description of gastric cancer and non-cancer with H. pylori detection was defined with modified Sydney Score System. Gastric mucosal tissue H. pylori DNA was extracted and genotyped for cagA mutation. Tissue IL-8 and cyclooxygenase-2 (COX-2) mRNA expression were conducted by real time relative quantitation polymerase chain reaction. From 17 Japanese advance gastric cancer and 12 benign gastric tissue samples, all were tested for genetic expression with same methods as well as Thai gastric mucosal tissue samples. The multivariate analysis was used for the risk study. Correlation and standardized t -test were done for quantitative data, P value < 0.05 was considered as a statistically significant. Results: There is a high non cagA gene of 86.8 per cent in Thai gastric cancer although there are high yields of the East Asian type in the positive cagA. The H. pylori infection prevalence in this study is reported by combined histopathology and H. pylori IgG antibody test with 77.1% and 97.4% of sensitivity and specificity, respectively. The serum PG I/II ratio in gastric cancer is significantly lower than in the non-cancer group, P = 0.045. The serum PG I/II ratio of less than 3.0 and IL-8 mRNA expression ≥ 100 or log10 ≥ 2 are significant cut off risk differences between Thai cancer and non-cancer, P = 0.03 and P < 0.001, respectively. There is a significantly lower PGI/II ratio in Japanese than that in Thai gastric cancer, P = 0.026. Serum PG I/II ratio at cut off less than 3.0 and IL-8 mRNA expression Raw RQ ≥ 100 or log 10 ≥ 2 are significantly difference between Thai cancer group when compared to non-cancer group, P = 0.013 and P < 0.001, respectively. In the correlation study, low PG I/ II ratio does not associate with chronic atrophic gastritis severity score in Thais non-cancer cases. However, there is a trend, but not significant convert correlation between IL-8 mRNA expression level and low PG I/II ratio in Thai positive H. pylori infection. The high expression of IL-8 gene demonstrates a poorer prognosis by stage and histology. Conclusion: Predominant gastric mucosal IL-8 mRNA expression level, H. pylori infection, and low PG I/II ratio are relative risks for Thai gastric cancer without correlation with cagA mutation. © 2013 Baishideng. All rights reserved.